Serum Neutralizing Antibody Titers 12 Months After Coronavirus Disease 2019 Messenger RNA Vaccination: Correlation to Clinical Variables in an Adult, US Population. (11th July 2022) - Zhao, Min; Slotkin, Rebecca; Sheth, Amar H; Pischel, Lauren; Kyriakides, Tassos C; Emu, Brinda; McNamara, Cynthia; Shi, Qiaosu; Delgobbo, Jaden; Xu, Jin; Marhoffer, Elizabeth; Mercer-Falkoff, Aleagia; et al.
Abstract: Background: We studied whether comorbid conditions affect strength and duration of immune responses after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) messenger RNA vaccination in a US-based, adult population. Methods: Sera (before and after BNT162b2 vaccination) were tested serially up to 12 months after 2 doses of vaccine for SARS-CoV-2-anti-Spike neutralizing capacity by pseudotyping assay in 124 individuals; neutralizing titers were correlated to clinical variables with multivariate regression. Postbooster (third dose) effect was measured at 1 and 3 months in 72 and 88 subjects, respectively. Results: After completion of primary vaccine series, neutralizing antibody half maximal inhibitory concentration (IC50) values were high at 1 month (14-fold increase from prevaccination), declined at 6 months (3.3-fold increase), and increased at 1 month postbooster (41.5-fold increase). Three months postbooster, IC50 decreased in coronavirus disease (COVID)-naïve individuals (18-fold increase) and increased in prior COVID 2019 (COVID-19+) individuals (132-fold increase). Age >65 years (β = −0.94, P = .001) and malignancy (β = −0.88, P = .002) reduced strength of response at 1 month. Both neutralization strength and durability at 6 months, respectively, were negatively affected by end-stage renal disease ([β = −1.10, P = .004]; [β = −0.66, P = .014]), diabetes mellitus ([β = −0.57, P = .032]; [β = −0.44, P = .028]), and systemic steroid use ([β = −0.066, P = .032]; [β = −0.55, P = .037]). Postbooster IC50 was robust against WA-1 and B.1.617.2. Postbooster neutralization increased with prior COVID-19 (β = 2.9, P < .0001), and malignancy reduced neutralization response (β = −0.68, P = .03), regardless of infection status. Conclusions: Multiple clinical factors affect the strength and duration of neutralization response after primary series vaccination, but not the postbooster dose strength. Malignancy was associated with lower booster-dose response regardless of prior COVID infection, suggesting a need for clinically guided vaccine regimens. Abstract : Multiple clinical factors affect the half maximal inhibitory concentration strength and duration after primary series vaccination. All subjects, regardless of prior coronavirus disease infection, had enhanced neutralization following the third dose. Malignancy decreased response after the third dose, suggesting the importance of clinically guided vaccine-dosing regimens.